Membudayakan Hidup Hemat Bagi Anak Di SDK Santo Yoseph Kuaputu Melalui Gerakan Gemar Menabung Sejak Dini - Fransiskus X. Sole; Gregorius J.E Kian; Cornelia Augustin Mutiara Wahi; Albertiana Susilo Dajum; Maria Elsiana Reta Huler; Nelsia Maria Dasilva; Trivonia Milburga Dewi; Siprianus S. Senda (AMMA : Jurnal Pengabdian Masyarakat, 2023)
Saving is an art of managing finances by setting aside money and saving it for later use when there is an urgent need. Knowledge and skills in managing finances should be instilled in early childhood. Children need to be given an understanding so that they are skilled at managing finances from a young age and it will benefit them in the future. The target of this community service activity is the children of Oemasi Village with an age range of 6 to 12 years who are at the Santo Yoseph Catholic Elementary School of Kuaputu. The method used is to provide knowledge about saving to children through dialogue, quiz games and distributing piggy banks to train children's knowledge and skills in saving. As a result, children have understanding and a willingness to save.